USING THE FACTORIAL CORRESPONDENCE ANALYSIS TO DETERMINE THE RISKS OF WATER RELATED DISEASES, HYGIENE AND GOOD PRACTICES WITH SURVEY DATA IN GHARB AREA, MOROCCO - Alwashali, Ebrahim; Jghalef, Boubker; Fadli, Mohammed (European Scientific Journal, ESJ, 2014)
Water related diseases, hygiene and good practices in Gharb area have been a major health problem especially in the rural areas. This investigation concerns the cities under such conditions in the region of: Kenitra, Sidi-Kacem and Sidi-Slimane. In this paper, we interpreted the case of water-related diseases in the region of the case study section diseases. Second step is to locate the main causes of the study in each city by the factorial correspondence analysis (FCA)using the SphinxV5 software. Kenitra city is characterized by the dominance of anemia followed by hepatitis and ascariasis. This is as a result of absence of good drinking tap water, going to the bathroom (always) during cooking, home not connected to the sewage network, poor toilet facilities and toilet papers thrown into the wastewater network. The city of Sidi-Kacem is characterized by candidacies, poor drinking tap water, people swimming in lakes, people eating fruits and vegetables without washing, finding the visual quality of the water (can leave deposits), people visiting the toilet during cooking, frequent changing of underwear (per week), people (rarely) wash their hands before cooking and solid waste near homes. Finally, the city of Sidi-Slimane is characterized by the trachoma which is accompanied by diarrhea and malnutrition; thus, this diseases is caused due to bad drinking water from "Saguia" village, people (rarely) washing their hands before cooking, home exposed to sewage and the use of septic tank type toilet